2015
DOI: 10.1039/c5ra07232h
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in vitro non-enzymatic glycation on biophysical and biochemical regimes of human serum albumin: relevance in diabetes associated complications

Abstract: Early glycation involves attachment of glucose on 3-NH 2 of lysine residues. Human serum albumin (HSA), a lysine rich protein, is highly prone to non-enzymatic glycation. In this study, the effect of different concentrations of glucose on HSA through early glycation was assessed by various physicochemicaltechniques. An early glycation product Amadori HSA was estimated by colorimetric method, nitro blue tetrazolium (NBT) and thiobarbituric acid assay (TBA). The conformational changes were confirmed by UV-visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 38 publications
(64 reference statements)
2
11
0
Order By: Relevance
“…The78.3% hyperchromicity in UV absorbance values forOH • -MG modifiedIgGas compared to 55.9% and 64.7% for OH • -IgG and MG-IgG samples, when compared with N-IgG, suggests a stronger structural damage of IgG by OH • -MG. IgG modified by OH • -MG reflect highly exposed chromophoric aromatic amino acid residues, indicating extensive structural perturbations in the molecule.Appearance of a hump like structure in MG-IgG and OH • -MG-IgG indicate the formation of AGEs. Similar changes in absorbance have been reported earlier[45, 46]. Fluorescence spectroscopy is a valuable parameter to monitor microenvironment around aromatic amino acid residues [47].…”
Section: Discussionsupporting
confidence: 79%
“…The78.3% hyperchromicity in UV absorbance values forOH • -MG modifiedIgGas compared to 55.9% and 64.7% for OH • -IgG and MG-IgG samples, when compared with N-IgG, suggests a stronger structural damage of IgG by OH • -MG. IgG modified by OH • -MG reflect highly exposed chromophoric aromatic amino acid residues, indicating extensive structural perturbations in the molecule.Appearance of a hump like structure in MG-IgG and OH • -MG-IgG indicate the formation of AGEs. Similar changes in absorbance have been reported earlier[45, 46]. Fluorescence spectroscopy is a valuable parameter to monitor microenvironment around aromatic amino acid residues [47].…”
Section: Discussionsupporting
confidence: 79%
“…We also found the newly generated chromophores in the event of glycation; a new characteristic peak of significant absorbance could be seen between 300 and 400 nm . It suggested that MGO induced a structural alteration of BSA and AGEs was generated …”
Section: Resultsmentioning
confidence: 65%
“…Tissue AGE deposition is largely responsible for complications arising in diabetes [36]. It also limits the antioxidant properties of HSA which depends on the presence of free thiol groups [37].…”
Section: Discussionmentioning
confidence: 99%